An innovation system perspective of two dairy value chains in Kerala - SREERAM, V; GUPTA, JANCY (The Indian Journal of Animal Sciences, 2018)
Although recognized that collaborative performance of the diverse actors are crucial for the success of a value chain, there have been few efforts to understand their dynamics of linkages and interactions in context of dairying. This study fills the gap by analysing the convergence among various actors of 2 dairy value chains (SBCMSS and PDDP) with an innovation system focus. Key informant interviews supplemented with household level suvey among the livestock rearers were conducted to collect data. Snowball sampling was followed to identify diverse actors of value chains followed by simple random sampling for mapping the innovation system. Data were analysed using Social Network Analysis (SNA). Results indicate that dairy farmers hold the key influencive position in the ego network of SBCMSS and the private dairy firm in case of PDDP. However, the network members of SBCMSS were more likely to access various resources and services than that of PDDP. Besides, there is a considerable scope for enhancing the linkages among the actors for better interaction. Higher centrality measures for the farmers in terms of information brokerage and proximity to the other actors were desirable results for the future extension and technology dissemination interventions. Policy makers could focus on fixing the gaps in linkages between the actors and reconfiguring the interactions to strengthen the central actors to improve the performance of innovation system.